Dynamic extension to energise young farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A report from Cameroon about how the work of one inspiring extension officer has dramatically benefited a group of young people. Working as a common initiative group, they have learned how to use modern, highly productive farming methods, and their farming has been so successful that they are looking to expand their cropping area.